FACTORS ASSOCIATED WITH PRELACTEAL FEEDING IN AFAR REGIONAL STATE, NORTHEASTERN ETHIOPIA: A CROSS SECTIONAL STUDY - Legesse Liben, Misgan; Wuneh, Abel Gebre; Zepro, Nejimu Biza; Mulugeta, Afework (International Journal of Research -GRANTHAALAYAH, 2017)
Introduction: Proper infant and young child feeding is critical for child health and survival. Despite of this fact, prelacteal feeding is still common in different parts of the world. Therefore, this study was conducted to assess prelacteal feeding practices and associated factors among mothers of children aged 6-23 months in Afar Regional State of Ethiopia. Methods: A community based cross sectional study was conducted in 2016 in Afar Regional State. A multistage cluster sampling was employed to select mothers of children aged 6-23 months. Data were cleaned, coded and entered into EpiData version 3.02. Then, data were exported to SPSS version 20 statistical package for analysis. Results: About 96% of the study children had ever breastfed. Of the mothers who had ever breastfed their index child, 42.9% [95 % CI: 39.0%, 47%] reported giving prelacteal feeds to their children. The most common prelacteal foods were raw butter (54.2%) and animal milk (28.5%). Being housewife, women of husbands without formal education, initiating breastfeeding after one hour of birth, having increased household income and lack of awareness on proper breastfeeding practices were associated with increased odds of prelacteal feeding practices. Conclusion: This study showed that nearly four women in every ten practiced prelacteal feeding. Therefore, health education and information programs on the advantages of early initiation of breastfeeding and the disadvantages prelacteal feeding at the village level for housewives, and strengthening health extension package could be important to hamper prelacteal feeding practices.